Evaluating information : - Katzer, Jeffrey (McGraw-Hill, 1991)
This book introduces students to social science research from the consumer’s point of view. The authors believe that while social science may not require that every student of the discipline will have to conduct research studies, it is still essential for students to successfully read, understand and evaluate the research published in their field. To that end, the authors of this text have streamlined their narrative, omitting the burden of technical jargon, and focusing on the broad elements common to all kinds of social science research, such as experimental, survey, and case study. Questions to Ask, found at the end of each chapter, highlight the specific criteria to consider when evaluating research and offer a clear and accessible presentation of the general principles in social science research.